IMF Staff papers : Volume 25 No. 3. (IMF Staff Papers; IMF Staff Papers, 1978)
This paper examines the relationship between increases in the money supply and inflation in four developing countries. It is first shown that the growth in the money supply and inflation are linked in a two-way relationship in these countries, and then a dynamic model is designed that explicitly introduces the link in the form of reactions of the government fiscal deficit to inflation. The basic hypothesis is that an increase in the rate of inflation, whatever its cause, increases the real value of the fiscal deficit, because money expenditures keep pace with inflation while nominal revenues tend to lag. The model is estimated for the four countries, and the empirical results tend to validate the hypothesis. It is found that fiscal deficits play an important role in the inflation process, and that increases in these deficits are largely owing to the differences in the lags of government expenditures and revenues. Two basic policy conclusions emerge from this study: first, the tendency of government budgetary positions to be automatically destabilizing in developing economies underscores the need for an actively anti-inflation fiscal policy in these economies. Second, developing countries should attach priority to tax reforms designed to eliminate revenue lags.